Etudes microbiologiques dans les eaux du littoral roumain de la Mer Noire - Mircea, V.; Șerbănescu, O. (Cercetări Marine - Recherches Marines, 2026)
The authors present the data obtained in 1971 by analyzing seawater samples collected from 20 stations, in which the total number of germs, anaerobic sulfite reducing and oil-oxidizing bacteria were determined.